The Responsiveness of the Lucerne ICF-Based Multidisciplinary Observation Scale: A Comparison with the Functional Independence Measure and the Barthel Index - Vanbellingen, Tim; Ottiger, Beatrice; Pflugshaupt, Tobias; Mehrholz, Jan; Bohlhalter, Stephan; Nef, Tobias; Nyffeler, Thomas (Frontiers in Neurology, 2016)
Background: Good responsive functional outcome measures are important to measure change in stroke patients. The aim of study was to compare the internal and external responsiveness, floor and ceiling effects of the motor, cognition & communication subscales of the Lucerne ICF-based Multidisciplinary Observation Scale (LIMOS) with the motor and cognition subscales of the Functional Independence Measure (FIM), and the Barthel Index (BI), in a large cohort of stroke patients. Methods: One hundred and eighteen stroke patients participated in this study. Admission and discharge score distributions of the LIMOS motor, LIMOS cognition & communication, FIM motor and FIM cognition, and BI were analyzed based on skewness and kurtosis. Floor and ceiling effects of the scales were determined. Internal responsiveness was assessed with t-tests, effect sizes (ES) and standardized response means (SRMs). External responsiveness was investigated with linear regression analyses. Results: The LIMOS motor and LIMOS cognition & communication subscales were more responsive, expressed by higher effect sizes (ES = 0.65, SRM = 1.17 and ES = 0.52, SRM = 1.17 respectively) as compared with FIM motor (ES = 0.54, SRM = 0.96) and FIM cognition (ES = 0.41, SRM = 0.88), and the BI (ES = 0.41, SRM = 0.65). The LIMOS subscales showed neither floor nor ceiling effects at admission and discharge (all < 15%). In contrast, ceiling effects were found for the FIM motor (16%), FIM cognition (15%) at discharge and the BI (at admission (22%) and discharge (43%). LIMOS motor and LIMOS cognition & communication subscales significantly correlated (p < 0.0001) with a change in the FIM motor and FIM cognition subscales, suggesting good external responsiveness. Conclusions: We found that the LIMOS motor and LIMOS cognition & communication, which are ICF-based multidisciplinary standardized observation scales, might have the potential to better detect changes in functional outcome of stroke patients, compared to the FIM motor and FIM cognition, and the BI.